A review of integrated advanced oxidation processes and biological processes for organic pollutant removal. Issue 3 (4th March 2022) - Nidheesh, Puthiya Veetil; Couras, Catia; Karim, Ansaf V.; Nadais, Helena
Abstract: Water pollution by recalcitrant organic contaminants is a recognized issue of significant concern since a wide range of these contaminants has been found in environmental matrices resulting in severe environmental and health issues. The role of wastewater treatment technologies is becoming more critical with the growing presence of these recalcitrant organic compounds in water. The removal of these compounds from environmental matrices has proved a difficult challenge for the scientific and technical community, as no single process is available for their degradation and mineralization. Advanced oxidation processes (AOPs) possess a great ability to treat a wide variety of these pollutants and to improve the biodegradability of wastewater. Still, they have some important drawbacks like high operational costs resulting from the consumption of energy and chemicals. In this framework, technological advancement, including the integration of AOPs with biological treatment, may help in reducing the pollutant concentration to the desired level, ensuring the better quality of water. This review addresses the combination of AOPs and biological processes used for the degradation of organic pollutants present in waters and wastewaters. Recent works on the combination of AOP and biological processes are summarized and discussed, including scientific, technical and economic aspects. Finally, conclusions and future perspectives for this line of research are presented.